Square planar versus tetrahedral NiS 4 cores in the coordination spheres of (HMB)Ru(II) and Cp*Ru(III) and a related CuS 4 complex. Synthetic, single-crystal X-ray diffraction, and magnetic studies {HMB = η 6-C 6Me 6 and Cp* = η 5-C 5Me 5} - Shin, R.Y.C. (2014)
10.1021/om050200p